Corporate Governance And Stakeholders' Financial Interests In Institutions Offering Islamic Financial Services - Grais, Wafik M., 1949- 1949- (The World Bank, 2006)
This paper focuses on the corporate governance arrangements of institutions offering Islamic financial services (IIFS) aimed at protecting stakeholders' financial interests. Many IIFS corporate governance issues are common with those of their conventional counterparts. Others are distinctive. In particular they offer unrestricted investment accounts that share risks with shareholders but without a voting right. This paper first reviews internal and external arrangements put in place by IIFS to protect stakeholders' financial interests. It discusses shortcomings notably in terms of potential conflict of interest between shareholders and holders of unrestricted investment accounts. It then suggests a corporate governance framework that combines internal and external arrangements to provide safeguards to unrestricted investment account holders without overburdening IIFS' financial performance. The paper uses a review of 13 IIFS and regulatory information from countries where IIFS have developed the most